Myths and Fallacies about Male Contraceptive Methods: A Qualitative Study amongst Married Youth in Slums of Karachi, Pakistan - Nishtar, Noureen (Glob J Health Sci, 2013)
Pakistan presently has one of the largest cohorts of young people in its history, with around 36 million people between the ages of 15 and 24 years. One of the main reasons for high population growth in Pakistan is almost stagnant contraceptive prevalence rate of 30% nationally and 17.4% amongst youth. The study was conducted to explore the perceptions regarding myths and fallacies related to male contraceptive methods among married youth aged 18-24 year in Karachi, Pakistan. Qualitative exploratory study design was adopted and a total of eight Focus Group Discussions (FGDs) were conducted. Study was conducted in two Union Councils of Korangi Town in the squatter settlement of Karachi, Pakistan from July to September 2010. Thematic analysis was done manually. General, physical, sexual, psychological, socio-cultural and religious were the common categories which lead to myths and fallacies related to condoms use and vasectomy among the married youth. The foremost myth amongst male and female youth was that use of both condoms and vasectomy cause impotence in males. Additionally, condoms were thought to cause infections, backache and headache in males. Some youth of the area think that vasectomy is meant for prisoners only. In conclusion our findings suggest that the potential reasons behind low use of male contraceptive methods among youth of squatter settlement of Karachi were myths and fallacies about male contraceptive methods. There are some important policy implications like counseling of the couple through peers and well trained family planning service providers to address these myths and misconceptions from the minds of youth.